2021
DOI: 10.1016/j.chemosphere.2021.129889
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of legacy and novel brominated flame retardants in sediments along the Rhône River corridor in France

Abstract: Brominated flame retardants (BFRs) are anthropogenic compounds that are ubiquitous in most 6 manufactured goods. Few legacy BFRs have been recognised as persistent organic pollutants (POPs) 7 and have been prohibited since the 2000s. However, most BFRs continue to be used despite growing 8 concerns regarding their toxicity; they are often referred to as novel BFRs (nBFRs). While 9 environmental contamination due to chlorinated POPs has been extensively investigated, the levels and spatiotemporal trends of BFRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Concentrations of BDE-209 in biosolids rose from 1995 to 2008, with concentrations doubling approximately every 5 years, which provided an indication of the size of the environmental reservoir of BDE-209 (Covaci & Malarvannan, 2016). Concentrations of legacy BFRs including PBDEs along the river Rhone achieved peak concentrations from the mid-1970s to the mid-2000s, but have stabilised since the mid-2010s (Vauclin et al, 2021). Karakas et al (2020) reported that the greatest impact on the reduction of total PBDE concentrations in sediment taken from close to San Francisco, was achieved by a reduction in water column concentrations, i.e.…”
Section: Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of BDE-209 in biosolids rose from 1995 to 2008, with concentrations doubling approximately every 5 years, which provided an indication of the size of the environmental reservoir of BDE-209 (Covaci & Malarvannan, 2016). Concentrations of legacy BFRs including PBDEs along the river Rhone achieved peak concentrations from the mid-1970s to the mid-2000s, but have stabilised since the mid-2010s (Vauclin et al, 2021). Karakas et al (2020) reported that the greatest impact on the reduction of total PBDE concentrations in sediment taken from close to San Francisco, was achieved by a reduction in water column concentrations, i.e.…”
Section: Sedimentmentioning
confidence: 99%
“…Concentrations of BDE‐209 in biosolids rose from 1995 to 2008, with concentrations doubling approximately every 5 years, which provided an indication of the size of the environmental reservoir of BDE‐209 (Covaci & Malarvannan, 2016 ). Concentrations of legacy BFRs including PBDEs along the river Rhone achieved peak concentrations from the mid‐1970s to the mid‐2000s, but have stabilised since the mid‐2010s (Vauclin et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to sediment core data from Western Europe, the environmental levels of PBDEs levelled off or decreased from the late 1990s and early 2000s (Bogdal et al, 2008;Vauclin et al, 2021). On the other hand, some studies from other industrialized countries conducted in the early 2000s and 2010s, documented increasing sediment concentrations of PBDEs (Table 2).…”
Section: Legacy Popsmentioning
confidence: 99%
“…Considering their volatility, POPs (including PAHs) belong to a group of semi-volatile organic compounds (SOCs). Once discharged into the environment, SOCs can be dynamically distributed between the gas phase, particulate phase, and other surface media, then eventually distributed among the atmosphere [ 2 ], water [ 3 ], soil [ 4 ], sediment [ 5 ], and biota [ 6 ]. Compared with other SOCs, the relatively longer atmospheric half-lives help POPs migrate with airflow diffusion [ 7 ] over long distances to condense in remote regions.…”
Section: Introductionmentioning
confidence: 99%